Development of Chiller Simulation System - Muhammad Zuhairi bin Abdul Jalil; Nizamuddin Bin Razali; Khairul Anuar bin Abdul Rahman (ASEAN Journal of Science and Engineering, 2021)
Each student got their learning style. In skills institutions, students' learning styles are more visual and kinesthetic than auditory. This is because teachers who do not diversify the teaching system will impact their students. Besides, students will become bored and lose focus due to non-interactive teaching sessions. Teaching aids also act as a tool that can provide fun and a more profound interest in teaching content. Moreover, the application of high-tech skills that match with the era of the industrial revolution 4.0 will improve skills and knowledge. This study aims to improve the teaching quality for the Course DMC2333 Water Cooled Chiller and Air-Cooled Chiller course. In this study, researchers have chosen the ADDIE design model as a guide in developing this product. The evaluation was done using a questionnaire that has been certified by three experts in mechanical, especially in the field of Refrigeration and Air Conditioning. The items developed by the researcher are divided into three primary constructs, which are design, development, and functionality. Each section was divided into several things that help in answering the research questions. The findings found that all experts agreed with the items in the questionnaire. However, there are also comments and suggestions for improvement attached by each expert. The results of these comments and enhancements can help researchers further improve the product's effectiveness in the following study.